Computational analysis of hybrid GPL blood nanofluid flow over various stenosed arteries in the presence of a magnetic field - Kannigah Thirunananasambantham; Zuhaila Ismail; Lim Yeou Jiann; Amnani Shamjuddin (Alexandria Engineering Journal, 2025)
It is widely acknowledged that coronary artery disease is a prime reason for the increasing mortality rate across the world, highlighting the need for effective therapies and diagnostic methods. It has been demonstrated that magnetic fields and nanoparticles can contribute to the development of advanced therapies. This study addresses this critical issue by analysing the effect of an external magnetic field on the blood embedded with hybrid silver and gold nanoparticles in a varying occlusion of a cosine-shaped stenosed artery using COMSOL Multiphysics. The influence of hybrid nanoparticles on the blood flow behaviour is further analysed by manipulating the volume fraction of the nanoparticles. This study's novelty lies in demonstrating the effectiveness of magnetohydrodynamic and hybrid nanofluid in detecting and managing stenosis at different severity stages. By evaluating their performance across these stages, it offers valuable insights for medical practitioners. An approach based on generalised power laws is used to model the blood flow. An analysis of the physical parameters, such as velocity profiles and wall shear stress, is carried out through the use of graphs. The study found that in the presence of the external magnetic field, substantial reductions in shear stress and velocity profile occur as the severity of the stenosis increases. As a result of the addition of gold and silver nanoparticles, the diseased artery exhibits smoother flow with a decrease in recirculations and abnormal behaviour observed in the post-stenotic area. The combined use of an external magnetic field and a hybrid nanofluid can help improve blood flow in stenosed arteries. This study has important implications for the field of nanomedicine as well as targeted drug delivery in stenotic arteries, which is the future of personalised and precise medical treatments. The results suggest that applying hybrid silver and gold nanoparticles together with a magnetic field could be effective in managing stenosis at different severity stages, providing a promising approach for improving patient outcomes.